Comparative Clinical Study of Efficacy and Safety of Benzoyl Peroxide Gel Versus Adapalene Gel as Monotherapy for the Treatment of Mild to Moderate Acne Vulgaris - Dr. Hezha Abdullah Ali; Dr. Saba Ali Rasheed (Academic Journal of Clinicians, 2022)
Background: Acne vulgaris disease is a common dermatological public health problem affecting adolescents and young population. Many topical agents are used for treatment of mild to moderate acne vulgaris with different efficacy and adverse effects. Objective: To compare between Adapalene and Benzoyl peroxide for the treatment of mild to moderate acne and to assess the efficacy, sid effects and tolerability of both of them. Methodology: A randomized comparative study carried out in Erbil Dermatology Teaching center in Erbil city-Kurdistan region/Iraq during the period from 1st of April to 31st of August, 2021 included one hundred patients with mild to moderate acne vulgaris and randomized into two equal groups to be treated either with Adapalene or Benzoyl peroxide, all patients were followed up and the treatment outcomes were reported Results: The mean number of inflammatory lesions, non-inflammatory lesions, total lesions and acne scores for patients of both groups were significantly reduced after 8 weeks treatment duration (p<0.001). However, a significant higher decline in number of non-inflammatory and total lesions in Adapalene group than benzoyl peroxide group. Similarly, skin oiliness decrease after 4 or 8 weeks treatment with Adapalene was significantly higher than oiliness decrease for patients treated with Bezoyl peroxide after 4 or 8 weeks. The adapalene application is related to moderate dryness and peeling, while benzoyl peroxide is related to itching or burning. Conclusions: Topical Adapalene therapy is more efficacious and tolerable than Benzoyl peroxide in management of mild to moderate acne vulgaris